KAJIAN PENANGANAN SEDIMENTASI DENGAN WADUK PENAMPUNG SEDIMEN PADA BENDUNGAN SERBAGUNA WONOGIRI - Sardi, Sardi; Kironoto, Bambang Agus; Jayadi, Rachmad (Civil Engineering Forum Teknik Sipil, 2008)
High rate of sedimentation in Wonogiri Multipurpose Dam may cause the dam service period to become shorter than the prior plan. The discharge of Wonogiri Multipurpose Dam is an accumulation of inflow from several main rivers, including Keduang River which is located at the east side of the dam. Keduang River supplies very high sedimentation input to the reservoir. One of the steps studied and to be implemented in the sediment countermeasure was the building of sediment pocket dam in Keduang River mouth before it enters the reservoir. The research was conducted to determine the reservoir sedimentation before and after countermeasure through a mathematical model approach. It was done by doing flow and sediment transport simulation using the NCCHE-GUI Program to calculate deposition in the reservoir. Simulation was carried out in existing condition and the condition after the sediment pocket dam was built, with the assumption that discharge was evenly distributed for each month. This simplification method was applied in wich monthly simulation was done for one hour. Simulation result was then multiplied by the number of hours allocated per month to generate the result for one year period. Simulation result indicates that annually sedimentation reduction or net deposition is 30.41% in average after the treatment by sediment pocket dam. It is also identifed from the simulation result that the reduction is relatively small, since simulation was not performed up to the condition where the pocket dam was already filled up by sediment, in which the flushing process has not been optimally simulated.